NILAI-NILAI PENDIDIKAN AKHLAK DALAM NOVEL “NEGERI 5 MENARA” KARYA AHMAD FUADI - Naili Nur Fadzilah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
This research was conducted because of the uniqueness found in the novel Negeri 5 Menara by Ahmad Fuadi. Among them is that this novel is able to provide inspiration and motivation for its readers, because in this novel it is presented in light and easy-to-understand language and is full of moral education values. based on some of these uniqueness, researchers are interested in making the novel Negeri 5 Menara as an object of research with the title